PERANCANGAN APLIKASI ABSENSI KELAS BERBASIS SMS GATEWAY - Muhammad Rasyidan; Andie Andie; M. Iqbal Firdaus (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
Student attendance data collection system is a computer-based data collection system to welcoming students to use computer applications. This application is designed to record the presence and activity of the students when carrying out learning activities in the classroom the Islamic University of Kalimantan (UNISKA) Muhammad Arsyad Al-Banjari Banjarmasin. This computer application is useful for lecturers to shorten the time in the process of recording student attendance and can be used to find data activeness of students in learning activities in order to follow the practical activities can run smoothly and more efficiently. In addition, because the data has been computerized the level of data security is guaranted by shunt of human error. In addition, with the application-based SMS Gateway, SMS will be sent automatically when there are students who do not attend. SMS will provide information on the on going study and ask why students do not attend. Therefore, students can respond to the text message, and if there is no response, then the student is deemed no news or negligent. Keyword: absent, class, sms gateway